Trend of Sensitivity Pattern of Uropathogenic Escherichia coli: Five Year Experience at a Tertiary Care Hospital in Dhaka (Journal of Shaheed Suhrawardy Medical College, 2013)
Background: Urinary tract infections are among the most common bacterial infections caused by pathogens with a decreasing susceptibility to several classes of antimicrobials.Objective: The purpose of the present study was to see the trend of sensitivity pattern of Escherichia coli (E. coli) isolated from the urinary tract patients.Methodology: This retrospective study was conducted at Uttara Adhunik Medical College Hospital, Dhaka from 2008 to 2012 for a period of 5(five) years. All patients were within ages 1 month to 80 years, comprising of both male and female, either out or in patients were included as study population. Urine sample was collected and Escherichia coli was isolated and identified as well as the antimicrobial susceptibility patterns was determined.Results: A total number of 16,666 urine samples were collected. No significant changes of susceptibility pattern of Escherichia coli was found to ciprofloxacin, cephradine, ceftriaxone, levofloxacin,  nalidixic  acid,  imipenem  and  meropenem;  however,  significant  change  was  detected  to amoxicillin, amoxiclav, cefixime, trimethoprim-sulfamethoxazole, amikacin, ceftazidime and mecillinam between 2008 and 2012.Conclusion: Trend of sensitivity pattern of Escherichia coli is changing to few important antibiotics.DOI: http://dx.doi.org/10.3329/jssmc.v5i2.20766J Shaheed Suhrawardy Med Coll, 2013;5(2):103-105